Space and identity in Jesús de Machaca (La Paz, Bolivia). Archeology, ethnography and historiography: a proposal for spatial analysis - Arano Romero, Salvador (2021)
In this paper we make a proposal for spatial analysis with archaeological, ethnographic and historiographic data on the Pacajes groups settled in Jesús de Machaca (La Paz, Bolivia), identifying different types of space: physical, administrative, symbolic and social. We call this network of spaces: spatialities, which directly and indirectly reflects the daily relationship between subjects and their environment. This work focuses particularly on the transitional period between the Inka conquest and the Spanish conquest. From the material data and oral sources, it was possible to determine that there is a signification and resignification of the different spatialities that were formed thanks to the interaction of the local inhabitants and the conquerors, where some of these aspects could remain in force.